Klasifikasi Genre Musik Menggunakan Machine Learning - Garda Zidane Dhamara; Sucipto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study examines the implementation of music genre classification using Machine Learning to develop an accurate and efficient music recommendation application. The main problem addressed is the automatic identification of music genres to improve recommendation personalization. The method used involves applying Machine Learning algorithms to a music dataset. The objective of this research is to build a system capable of automatically classifying music genres and serving as a foundation for a smarter recommendation system. Preliminary results indicate that Machine Learning is effective in music grouping, which will contribute to increased recommendation accuracy. This research is expected to make a significant contribution to the development of intelligent music applications.